Penerapan Sistem Manajemen Mutu ISO 9001: 2015 Di SMK Negeri 4 Banjarmasin - Fitria Wulandari; Zainal Arifin; Subiyantoro Subiyantoro; Sedya Santosa (Studia Manageria, 2021)
This study aims to find out 1) What are the stages of implementing the ISO 9001:2015 quality management system at SMK Negeri 4 Banjarmasin and 2) What is the impact of implementing the system on the work system and work culture in schools. This research is a field research with a qualitative descriptive approach. The process of collecting data was carried out by observing, then interviewing the Deputy Principal for Quality Management and equipped with some documentation. The data analysis that the researcher uses with the Miles and Huberman Model is condensation, data presentation and conclusions/verification. The results of this study indicate that: 1) several stages carried out by SMK Negeri 4 Banjarmasin in implementing the ISO 9001:2015 quality management system are a ) attend training with the guidance of a consultant, b) prepare quality documents and implement a quality management system according to documents prepared by the school, c) internal audit coordinated by the Quality Management Deputy, d) external audit conducted by PT. URS Service Indonesia, and e) granting of ISO 9001:2015 certificate/ Institutional certification. The impact of the implementation of ISO 9001: 2015 is the creation of a better work system, organized according to procedures and can create a team work culture that upholds solidarity and work professionalism.